2007
DOI: 10.1002/chin.200728187
|View full text |Cite
|
Sign up to set email alerts
|

New Diphenyl Ethers from the Insect Pathogenic Fungus Cordyceps sp. BCC 1861.

Abstract: New Diphenyl Ethers from the Insect Pathogenic Fungus Cordyceps sp. BCC 1861. -The glycosides cordyol A (Ia) and B (Ib) and the diphenyl ether cordyol C (II) are isolated. (II) exhibits significant anti-HSV-1 activity and cytotoxic activity against BC and NCI-H187 cancer cell lines. -(BUNYAPAIBOONSRI*, T.; YOIPROMMARAT, S.; INTEREYA, K.; KOCHARIN, K.; Chem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…[10,11], Leathesia nana [12], Phyllanthus atropurpureus [13], Symphyocladia latiuscula [14], and so on. Diphenyl ethers exhibit a wide range of interesting biological activities, such as antimicrobial [1,3,6,8,10], cytotoxic [2,6,9], radical-scavenging [11], enzyme inhibitory [5], actin inhibitory [15], anti-HSV-1 [2], and phytocidal activities [16,17]. In early chemical investigation, we reported the isolation of two diphenyl ethers, 2-isopentenyldiorcinol (9) and diorcinol (10), from a strain of endolichenic fungus Aspergillus sp.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…[10,11], Leathesia nana [12], Phyllanthus atropurpureus [13], Symphyocladia latiuscula [14], and so on. Diphenyl ethers exhibit a wide range of interesting biological activities, such as antimicrobial [1,3,6,8,10], cytotoxic [2,6,9], radical-scavenging [11], enzyme inhibitory [5], actin inhibitory [15], anti-HSV-1 [2], and phytocidal activities [16,17]. In early chemical investigation, we reported the isolation of two diphenyl ethers, 2-isopentenyldiorcinol (9) and diorcinol (10), from a strain of endolichenic fungus Aspergillus sp.…”
Section: Introductionmentioning
confidence: 98%
“…16-20-8-1) was re-fermented at the same scale. Further chemical investigation was carried out, which led to the isolation of eight compounds with the character of diphenyl ether structure, including four sterigmatocystins (1)(2)(3)(4) and four diphenyl ethers (5)(6)(7)(8). Among them, there were two new compounds, oxisterigmatocystin D (1), 9-acetyldiorcinol B (6), and six known compounds, oxisterigmatocystin A (2) [20], oxisterigmatocystin C (3) [20], sterigmatocystin (4) [21], diorcinol B (5) [22], violaceol-I (7) [23] and violaceol-II (8) [23] (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The cytotoxic activities of other diphenyl ethers and their derivates in neoplastic cell lines have been observed by other authors as well. Bunyapaiboonsri et al (2007) isolated two new glycosidic diphenyl ethers (cordyol A and B) and a diphenyl ether (cordyol C) from the fungus Cordyceps sp, and performed cytotoxic tests with all three substances in two different cell lines (BC -breast cancer, and NCI-H187 -lung cancer). They found that only cordyol C had moderate cytotoxic activity against both cell lines, with an IC 50 of 8.65μg/ml and 3.75 μg/ mL for BC and NCI-H187, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…C. sinensis also contains polysaccharides, which account for anti-inflammatory, antioxidant, antitumor, antimetastatic, immunomodulatory, hyperglycemic, steroidogenic, and hypolipidemic effects (158,159). New diphenyl ethers (cordyols A-C, Q6-Q8) were discovered recently in Cordyceps (161). Q6 was associated with significant anti-HSV (herpes simplex virus) activity (161).…”
Section: Cordyceps Sinensis (Tung Chung Hsia Tsao)mentioning
confidence: 99%